A clinic-epidemiological study of 148 patients of pemphigus at Lady Reading Hospital, Peshawar: a case series - Mohammad Majid Paracha,; Sagheer, Farah; Abdul Qayyum Khan, (Journal of the Pakistan Medical Association, 2023)
A seven-year retrospective study was held at the Department of Dermatology, Lady Reading Hospital, Peshawar, between 2013 to 2020 to determine the demography and clinical features of pemphigus. Among 148 patients included in this study 88 (58%) were females and 60 (40%) were males with a female to male ratio of 1.46:1. Average age at onset of the disease was 38±12 years (range 14-75 years). On the basis of Autoimmune Bullous Skin Disorder Score (ABSIS), 14 (9.3%) patients had mild disease, 58 (38.7%) had moderate disease, and 76 (50.7%) patients had severe disease. In total, 144 (96%) patients had pemphigus vulgaris, 3 (2%) patients had pemphigus foliaceous and 1 (0.7%) patient had paraneoplastic pemphigus. Severe pemphigus was more frequently associated with multiple relapses (p=0.00). This study shows poor prognostic factors like severe pemphigus vulgaris associated with multiple relapses. ---Continue